Blockchain basics : a non-technical introduction in 25 steps - Drescher, Daniel, ....- (New York : Apress, 2017)
In 25 concise steps, you will learn the basics of blockchain technology. No mathematical formulas, program code, or computer science jargon are used. No previous knowledge in computer science, mathematics, programming, or cryptography is required. Terminology is explained through pictures, analogies, and metaphors. This book bridges the gap that exists between purely technical books about the blockchain and purely business-focused books. It does so by explaining both the technical concepts that make up the blockchain and their role in business-relevant applications. What You'll Learn * What the blockchain is * Why it is needed and what problem it solves * Why there is so much excitement about the blockchain and its potential * Major components and their purpose * How various components of the blockchain work and interact * Limitations, why they exist, and what has been done to overcome them * Major application scenarios Who This Book Is For Everyone who wants to get a general idea of what blockchain technology is, how it works, and how it will potentially change the financial system as we know it